Foreign economic and macro policies after the US presidential election - Markus Jaeger (EconPol Forum, 2024)
Foreign trade and macroeconomic policies under a Harris administration would largely provide for continuity with the Biden administration, while policies under another Trump administration would have the potential to be highly disruptive. Regardless of who becomes the next president, US national-security-focused trade and investment policies will continue to be tightened in the context of US-Chinese strategic competition. Trump trade policies could prove hugely destabilizing to international trade, severely strain US-EU trade relations, and lead to a full-blown trade war with China. Fiscal policy will remain loose under both a Harris and a Trump administration, but the latter would also seek to pressure the Federal Reserve to pursue loose monetary and weak dollar policies. The EU should ready its new geoeconomic instruments to deter US discriminatory measures, while signaling openness to negotiations about how best to defuse transatlantic economic conflict.
Keywords: 330